To rearrange the area formula for a trapezoid, \( A = \frac{1}{2} h (b_1 + b_2) \), for \( h \), we follow these steps:
-
Start with the original formula: \[ A = \frac{1}{2} h (b_1 + b_2) \]
-
Multiply both sides by 2: \[ 2A = h (b_1 + b_2) \]
-
Divide both sides by \( (b_1 + b_2) \): \[ h = \frac{2A}{b_1 + b_2} \]
Thus, the correct rearranged formula for \( h \) is: \[ h = \frac{2A}{b_1 + b_2} \]
From the provided options, this corresponds to: h equals Start Fraction 2 upper A over b subscript 1 baseline plus b subscript 2 baseline End Fraction.